Internet of Things (IoT) in Education: A Bibliometric Review - Abdullah, Khairul Hafezad; Gazali, Novri; Muzawi, Rometdo; Syam, Elgamar; Roslan, Mohd Firdaus; Sofyan, Davi (International journal of information science and management, 2024)
The Internet of Things (IoT) has made our surroundings more innovative and responsive, which has improved our lives. This research aims to provide a comprehensive overview by describing the descriptive parameters of publications, visualizing co-authorship and citation patterns, extracting the authors' keywords, and determining the impact and research performance of the IoT in education. Subsequently, this paper provides an orientation for researchers to understand better the main progress and gaps in this scientific publication. From 2006 to 2021, a comprehensive inspection of 2503 documents in the Scopus database was accomplished. Based on the findings, the number of publications increased steadily, with a hike in publication numbers in 2020. Scholars from China contributed approximately 467 of the total global publications among 103 other countries. In addition, of the other 160 outlets, Advances in Intelligent Systems and Computing was the most prolific source title. Generally, there is sustained interest and increased research in this field, apart from establishing novel methods and directions. Accordingly, an in-depth examination of the IoT in education research may assist researchers and practitioners in advancing prospective knowledge in this subject by identifying gaps.